The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1159/000381201
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Exercise before or after Bariatric Surgery: A Systematic Review

Abstract: Background: Bariatric surgery has a considerable effect on weight loss. A positive relation of exercise and weight loss has been described before. However, the mode of exercise and its timing pre- or postoperatively or a combination remains unclear. Methods: A multi-database search was conducted. Identified articles were reviewed on description of exercise, timing around a bariatric intervention, and outcome. Methodological quality of the included studies was rated using the Physiotherapy Evidence Database sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 45 publications
(99 reference statements)
2
45
0
2
Order By: Relevance
“…Regarding the both physically active operated and non-operated groups, was verified difference only on the variable age. Supporting these results, other studies made evident the relation between the regular practice of physical activity and an enhancement of the functional capacity and quality of life of operated patients 12 , 14 , 21 , 25 .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Regarding the both physically active operated and non-operated groups, was verified difference only on the variable age. Supporting these results, other studies made evident the relation between the regular practice of physical activity and an enhancement of the functional capacity and quality of life of operated patients 12 , 14 , 21 , 25 .…”
Section: Discussionsupporting
confidence: 61%
“…Nevertheless, there are evidences that regular physical activity practice promotes an enhancement on the physical fitness parameters, and it contributes directly to the functional capacity and quality of life of the operated individuals 14 , 21 , 25 . Healthy lifestyle, including a healthy food intake and regular physical activity practice, contributes not only to the maintenance of the positive results acquired with the surgery, but also to the general health conditions of these patients 1 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that loss of lean body mass may be substantial after surgery for obesity and weight-related diseases [424, 425]. In a recent systematic review of the literature, the majority of reports found positive effects of exercise before and following surgery for obesity and related diseases on anthropometric parameters, cardiovascular risk factors and physical fitness [426]. In the long-term, higher physical activity and lower sedentary time is associated with greater excess weight loss and maintenance of reduced body weight following surgery for obesity and weight-related diseases [427].…”
Section: Chapter 4 General Considerations For Indications Of Surgery mentioning
confidence: 99%
“…World Health Organization (OHS) de ines obesity as excessive accumulation of adipose tissue with health implications, [2] with multifactorial etiology, [2][3][4] and can be classi ied as several grades according to BMI´s values over 40kg/ m² [3,5,6]. The importance of this study about obesity relates to its consequences in other diseases development, such as: diabetes mellitus type II; arterial hypertension; dyslipidemia; chronic obstructive pulmonary disease; heart disease and certain cancers [4,[6][7][8][9]].…”
Section: Introductionmentioning
confidence: 99%